14.THE EFFECT OF GINGER EXTRACTS ON BACTERIAL ISOLATES FROM PATIENTS WITH SUPPURATIVE OTITIS MEDIA AND EXTERNA: IN VITRO STUDY (Iraqi Journal of Medical Sciences, 2018)
Background: Otitis media is a group of complex inflammatory disorders affecting the middle ear, which can be acute or chronic. Otitis externa is an inflammation on the skin of the external auditory canal usually associated with secondary bacterial and/or fungal infection of macerated skin and subcutaneous cellular tissue.Objective: To determine the effect of ginger extracts on bacterial isolates from patients suffering from otitis.Methods: Two hundred patients suffering from suppurative otitis media and externa, who were attending to ENT Department, Al-Imamein Al-Kadhimein Medical City. The powder of ginger rhizomes was soaked with the solvent left in a shaking water bath at 40 °C for 24 hours and then filtered using Whatman No.1 filter paper. Each extract was concentrated using a rotary evaporator with vacuum to get the final crude extract after the procedure of ginger extract was done. The activity of this extract was tested against bacterial isolates from patients with otitis.Results: The results of this study revealed that otitis externa was less common infection than the other types of otitis 29 (14.5%), while acute otitis media comprised 96 (48.0%), and chronic suppurative otitis media consisted of 75 (37.5%). The most common bacterial isolates that caused otitis were Pseudomonas spp. followed by Staphylococcus spp. The results showed that, there are different effects among (chloroform, methanol, and aqueous) extracts of ginger against pathogenic bacteria.Conclusion: Generally, ginger extracts had a good effect on isolated bacteria. Chloroform extract was the most effective one, followed by methanol extract, while aqueous extract showed the least activity in this regard.Keywords: Otitis externa, otitis media, ginger extractionCitation: Mohammed MM, Al-Attraqchi AAF, Al-Hasseni JMK, Sahib HB. The effect of ginger extracts on bacterial isolates from patients with suppurative otitis media and externa: in vitro study. Iraqi JMS. 2018; 16(2): 216-222. doi: 10.22578/IJMS.16.2.14